Hybrid, Multi-Source, and Integrated Energy Harvesters - Bai, Yang; Jantunen, Heli; Juuti, Jari (Frontiers in Materials, 2018)
Energy harvesting is one of the most rapidly growing of the emerging technologies. This field has arrived at the hybrid and multi-source era, where hybrid structures and novel materials are able to boost the energy conversion efficiency and/or make the harvesters capable of benefitting from multiple energy sources simultaneously. Such hybrid and multi-source energy harvesters have not frequently been reviewed in the past, potentially because of the small number of publications compared to that of their single-source and individual counterparts. However, as their number is becoming larger, it is now necessary to give sufficient and frequent reviews of developments in the field. Furthermore, an increasing number of developed energy harvesters are moving out of the laboratory into industrial markets. In practice, energy harvesters need to be integrated with energy storage and/or end users such as sensors and wireless sensor networks. Therefore, the harvester-storage and harvester-sensor integration systems also need to be reviewed frequently. This mini-review includes works reported in the first half of 2018 and provides a timely update to the published review. It focuses on the above-mentioned hybrid and multi-source energy harvesters as well as on integrated harvesters, energy storage systems and end users (e.g. sensors), including CMOS (complementary metal-oxide-semiconductor) technology-based harvesters and systems.